Introduction to Special Issue: A Special Thematic Issue on Evolving Practices in Career Development - Goyer, Liette; Fournier, Geneviève (Canadian Journal of Counselling and Psychotherapy, 2012)
This special issue of the Canadian Journal of Counselling and Psychotherapy includes articles on changing career development practices dealing with skills related to social justice, evaluation of skills assessment, career conversations, and career self-management, as well as youth work transitions, the relational context in decision-making, and parental involvement in children’s career exploration.